Digital Scholarly Publishing and Archiving Services by Academic Libraries: Case Study of the University of Patras - Georgiou, Panos; Tsakonas, Giannis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
During the last years, dramatic changes in the electronic publishing landscape have created new roles and changed the traditional ones. Presently, some libraries have capitalised on their experience and knowledge in information technology and electronic publishing to undertake such activities, while at the same time they spearhead the campaign for Open Access spreading within academic communities. The Library & Information Centre (LIC) of the University of Patras (UoP), Greece, has been playing an active role in promoting Open Access (OA) in Greece. Since 2007, LIC has been experimenting with OA publishing practices and tools within the framework of various R&D projects. Two of the major results of these efforts are the ‘Pasithee’ e-publishing platform and the ‘Dexamene’ digital archive for Greek scholarly journals. Both platforms are based on OJS-Open Journal Systems e-publishing software. The two facilities were appropriately modified to meet the LIC’s publishing and archiving requirements respectively. Currently two journals are being hosted on each platform and all four are from the Humanities. The LIC is negotiating with more publishers and editorial teams to host their journals. In this article we focus on: - technical and managerial key issues of the development and operation phases, - services and procedures, - the business model, - technological, procedural and legal issues and problems that were encountered when working together with publishers, editors and authors, and - future plans for improving and upgrading our e-publishing services into an integrated institutional platform to cover all kinds of publications and data types (monographs, conference proceedings, teaching material, bulletins, magazines etc.). The article concludes with a succinct presentation of the Directory of Greek Digital Resources, a pilot infrastructure developed by the LIC which indexes and presents digital publishing initiatives in Greece and aims to become a formal registry of Greek scholarly resources in digital format.